Applications of smart materials in minimally invasive dentistry – some research and clinical perspectives - Par, M.; Cheng, L.; Camilleri, J.; Lingström, P. (Dental materials, 2024)
Dental caries is one of the most prevalent bacteria-induced non-communicable diseases globally. It is known to be the top oral health burden in both developing and developed nations. There is substantial literature on the disease process and there is still debate on the extent of caries removal needed and the adequacy of the materials available to restore the lost tooth structure. The current review discusses the disease process together with the contemporary management of the carious lesion and also presents substantial evidence on novel materials and techniques that make minimally invasive dentistry predictable. The written work presented shows the most relevant literature for the management of dental caries focusing on novel materials used in minimally invasive dentistry. There is still much to learn about specific antimicrobial and caries prevention mechanisms of novel materials. Materials that respond to a single or a few stimuli remain "weakly intelligent" in the face of the complex microenvironment in the oral cavity. Engineered systems that combine artificial intelligence and chemical engineering, are expected to possess higher intelligence, self-healing capabilities as well as environmental adaptability, and may be future promising research directions. The targeted approach in managing dental caries will hopefully have a better clinical outcome. The strategies discussed are alternatives to the contemporary approach and will improve the clinical management.